Sulfide solid electrolyte for all-solid-state battery negative electrode and its manufacturing method

By using sulfide solid electrolytes composed of lithium, sulfur, phosphorus and halogen elements in lithium secondary batteries, the safety hazards caused by liquid electrolyte leakage are solved, and by improving the discharge capacity and charging efficiency of the battery, a more comprehensive battery performance improvement is achieved.

CN111293351BActive Publication Date: 2025-04-04HYUNDAI MOTOR CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201910499968.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-10
Filing Date
2019-06-11
Publication Date
2025-04-04
Estimated Expiration
2039-06-11

AI Technical Summary

Technical Problem

The liquid electrolytes used in existing lithium secondary batteries are prone to leakage, resulting in safety hazards. The physical properties of all-solid-state batteries are relatively simple and there is a lack of more comprehensive research.

Method used

A new type of sulfide-based solid electrolyte is used, which includes lithium element, sulfur element, phosphorus element and halogen element. The molar ratio of sulfur element to phosphorus element is between 5 and 7, and the molar ratio of lithium element to phosphorus element is between 3 and 4. The electrolyte is produced by preparing raw materials, stirring and mixing, drying and heat treatment.

Benefits of technology

In the negative electrode application of all-solid state batteries, this sulfide-based solid electrolyte significantly improves the discharge capacity and charging efficiency of the battery and enhances the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111293351B_ABST
    Figure CN111293351B_ABST
Patent Text Reader

Abstract

The present application discloses a sulfide solid electrolyte suitable for an all-solid-state battery negative electrode and a method for manufacturing the same. The sulfide solid electrolyte may include lithium (Li), sulfur (S), phosphorus (P) and halogen (X), wherein the halogen (X) is selected from chlorine (Cl), bromine (Br), iodine (I) and a combination thereof, and the molar ratio (S / P) of sulfur (S) to phosphorus (P) is 5 to 7.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sulfide solid electrolyte suitable for an all-solid-state battery negative electrode and a method for manufacturing the same. Background Art

[0002] Secondary batteries have been widely used in large devices, such as vehicles and power storage systems, and small devices, such as mobile phones, camcorders, and notebook computers.

[0003] As devices to which secondary batteries are applied become more diverse, demands for improving the safety and performance of batteries increase.

[0004] Lithium secondary batteries, which are one type of secondary batteries, exhibit higher energy density and capacity per unit area than nickel-manganese batteries or nickel-cadmium batteries.

[0005] However, in most cases, a liquid electrolyte such as an organic solvent is used in such a lithium secondary battery. For this reason, the electrolyte may leak from the lithium secondary battery, and the lithium secondary battery may catch fire due to the leakage of the electrolyte.

[0006] Therefore, in recent years, all-solid-state batteries that use solid electrolytes instead of liquid electrolytes to improve the safety of lithium secondary batteries have attracted considerable attention.

[0007] Solid electrolytes exhibit non-flammability or flame retardancy. Therefore, the safety of solid electrolytes is higher than that of liquid electrolytes. In addition, solid electrolytes can be manufactured to have a bipolar structure. Therefore, the volume energy density of all-solid-state batteries can be increased to the extent that the volume energy density of all-solid-state batteries is about 5 times that of conventional lithium-ion batteries.

[0008] Solid electrolytes are classified as either oxide-based solid electrolytes or sulfide-based solid electrolytes. Sulfide-based solid electrolytes have higher lithium ion conductivity than oxide-based solid electrolytes and are stable over a wider voltage range. For these reasons, sulfide-based solid electrolytes are mainly used.

[0009] In recent years, sulfide-based solid electrolytes having an argyrodite-based crystal structure that is easily composited and exhibits high ionic conductivity have been actively studied.

[0010] However, research on sulfide-based solid electrolytes has focused on improving the physical properties of the material. Since sulfide-based solid electrolytes only constitute a component of all-solid-state batteries, more comprehensive research is needed.

[0011] The information included in this Background of the Invention section is only for enhancement of understanding of the general background of the invention and should not be taken as an acknowledgement or any form of suggestion that this information forms the prior art already known to a person skilled in the art. Summary of the invention

[0012] Various aspects of the present invention are directed to providing a sulfide-based solid electrolyte having a novel composition configured to exhibit excellent effects when used for a negative electrode of an all-solid-state battery.

[0013] The objects of the present invention are not limited to those described above. The objects of the present invention will be clearly understood from the following description and can be achieved by the means defined in the claims and their combinations.

[0014] Various aspects of the present invention relate to providing a sulfide solid electrolyte, which includes lithium element (Li), sulfur element (S), phosphorus element (P) and halogen element (X), wherein the halogen element (X) is selected from chlorine element (Cl), bromine element (Br), iodine element (I) and combinations thereof, and the molar ratio (S / P) of sulfur element (S) to phosphorus element (P) is 5 to 7.

[0015] The molar ratio (S / P) of sulfur element (S) to phosphorus element (P) may be 6 to 7.

[0016] The molar ratio (Li / P) of lithium element (Li) to phosphorus element (P) may be 3 to 4.

[0017] The sulfide-based solid electrolyte may be represented by Chemical Formula 1 below.

[0018] [Chemical formula 1]

[0019] Li a PS b X c

[0020] Among them, 3≤a≤4, 5≤b≤7, and 1≤c≤2.

[0021] The sulfide-based solid electrolyte may include an anion cluster P 2 S 7 4- .

[0022] Various aspects of the present invention are directed to providing an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the negative electrode may include a sulfide-based solid electrolyte.

[0023] Various aspects of the present invention are directed to providing a method for manufacturing a sulfide-based solid electrolyte, the method comprising preparing a sulfide-based solid electrolyte comprising elemental lithium, elemental sulfur, P 2 S 5 and raw materials of lithium halide (LiX), introducing the raw materials into a solvent and stirring the mixture, drying the stirred mixture, and heat-treating the dried material.

[0024] The sulfide-based solid electrolyte may include sulfur (S) selected from elemental sulfur, P 2 S 5 and at least one of a combination thereof.

[0025] The raw material may also include a selected from Li 2 S, elemental phosphorus, elemental halogen molecules and at least one of their combinations.

[0026] The step of preparing the raw material may include mixing simple lithium, simple sulfur, P according to the composition of the sulfide-based solid electrolyte represented by the above chemical formula 1. 2 S 5 and lithium halide (LiX).

[0027] The solvent may be selected from methanol, ethanol, propanol, butanol, dimethyl carbonate, ethyl acetate, tetrahydrofuran, 1,2-dimethoxyethane, propylene glycol dimethyl ether, acetonitrile, and combinations thereof.

[0028] The drying step may include vacuum drying at 25 to 200° C. for 2 to 20 hours.

[0029] The drying step may include a first drying performed at 25-45° C. and 1-3 hours, a second drying performed at 50-70° C. and 1-3 hours, a third drying performed at 100-120° C. and 1-3 hours, a fourth drying performed at 150-170° C. and 1-3 hours, and a fifth drying performed at 200-220° C. and 1-3 hours.

[0030] The heat treatment step may be performed at 400 to 600° C. for 1 to 10 hours.

[0031] Other aspects and exemplary embodiments of the invention are discussed below.

[0032] The methods and apparatus of the present invention have other features and advantages that are apparent or set forth in more detail in the accompanying drawings and the following detailed description incorporated herein, which together serve to explain certain principles of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic cross-sectional view showing an all-solid-state battery according to an exemplary embodiment of the present invention;

[0034] Figure 2 A flowchart schematically showing a method for manufacturing a sulfide-based solid electrolyte according to an exemplary embodiment of the present invention;

[0035] Figure 3 is a graph showing the measurement results of the discharge capacity of the all-solid-state battery according to Experimental Example 2; and

[0036] Figure 4 1 is a diagram showing the results of analyzing the sulfide-based solid electrolyte according to the example using X-ray photoelectron spectroscopy (XPS).

[0037] It should be understood that the attached drawings are not necessarily to scale, and they illustrate somewhat simplified representations of various features of the basic principles of the invention. The specific design features of the invention included herein, including, for example, specific size, orientation, location and shape will depend in part on the specific intended use and use environment.

[0038] In the drawings, reference numbers refer to the same or equivalent parts of the present invention throughout the several figures of the drawing. DETAILED DESCRIPTION

[0039] Reference will now be made in detail to various embodiments of the present invention, examples of which are illustrated in the accompanying drawings and described below. Although the present invention will be described in conjunction with exemplary embodiments of the present invention, it should be understood that this specification is not intended to limit the present invention to these exemplary embodiments. On the other hand, the present invention is intended to cover not only the exemplary embodiments of the present invention, but also various alternative forms, modifications, equivalent forms and other embodiments included within the spirit and scope of the present invention as defined by the claims.

[0040] The above-mentioned objects and other objects, features and advantages will be clearly understood according to the following exemplary embodiments with reference to the accompanying drawings. However, the present invention is not limited to these embodiments and can be implemented in different forms. The exemplary embodiments only provide a comprehensive and complete understanding of the disclosed content and fully inform the technical concept of the present invention to those skilled in the art.

[0041] It should be understood that when used in exemplary embodiments, the terms "including", "having", etc. refer to the existence of the stated features, numbers, steps, operations, elements, parts or a combination thereof, but do not exclude the existence or addition of one or more other features, numbers, steps, operations, elements, parts or a combination thereof.

[0042] Unless otherwise clearly stated in the context, all numbers, numerals and / or expressions representing the amount of components, reaction conditions, polymer compositions and mixtures used in this specification are approximate values, which reflect the various uncertainties of measurement inherently occurring when obtaining these numbers, etc. For this reason, it is understood that in all cases, the term "about" can be understood to modify all numbers, numerals and / or expressions. In addition, when a numerical range is included in the description, unless otherwise defined, these ranges are continuous and include all numbers (including the maximum value within the range) from the minimum to the maximum. In addition, when a range refers to an integer, unless otherwise defined, it can include all integers from the minimum to the maximum, including the maximum value within the range.

[0043] Figure 1 1 is a schematic cross-sectional view showing an all-solid-state battery 1 according to an exemplary embodiment of the present invention. Referring to the figure, the all-solid-state battery 1 includes a positive electrode 10, a negative electrode 20, and a solid electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20.

[0044] Lithium-ion batteries using liquid electrolytes can use only one electrolyte. However, since the all-solid-state battery 1 uses a solid electrolyte, different electrolytes can be used for the positive electrode 10, the negative electrode 20, and the solid electrolyte layer 30. Therefore, in the case of using a specific solid electrolyte optimized for the conditions or physical properties required for each component, the performance of the all-solid-state battery 1 can be further improved.

[0045] Various aspects of the present invention are directed to providing a sulfide-based solid electrolyte that can improve the discharge capacity and charge efficiency of a battery when used for the negative electrode 20. However, the sulfide-based solid electrolyte according to the exemplary embodiment of the present invention is not only used for the negative electrode 20, but can also be used for the positive electrode 10 and the solid electrolyte layer 30 without limitation.

[0046] The sulfide-based solid electrolyte according to an exemplary embodiment of the present invention includes lithium (Li), sulfur (S), phosphorus (P) and a halogen (X). The halogen (X) may be selected from chlorine (Cl), bromine (Br), iodine (I) and a combination thereof.

[0047] The sulfide-based solid electrolyte may be represented by Chemical Formula 1 below.

[0048] [Chemical formula 1]

[0049] Li a PS b X c

[0050] Among them, 3≤a≤4, 5≤b≤7, and 1≤c≤2.

[0051] The sulfide-based solid electrolyte is characterized in that the molar ratio (S / P) of sulfur element (S) to phosphorus element (P) is 5 to 7, preferably 6 to 7.

[0052] In addition, the sulfide-based solid electrolyte is characterized in that the molar ratio (Li / P) of lithium element (Li) to phosphorus element (P) is 3 to 4.

[0053] Sulfide-based solid electrolytes have a new composition, which is different from conventional sulfide-based solid electrolytes such as Li 6 PS 5 Cl, the molar ratio of sulfur to phosphorus (S / P) is higher, and the molar ratio of lithium to phosphorus (Li / P) is lower.

[0054] Only when the molar ratio of the elements of the sulfide-based solid electrolyte satisfies the above range, when the sulfide-based solid electrolyte is used for the negative electrode of the battery, the discharge capacity and the charge efficiency of the all-solid-state battery can be improved.

[0055] Figure 2 The flowchart schematically shows a method for manufacturing a sulfide-based solid electrolyte according to an exemplary embodiment of the present invention. Referring to the figure, the method for manufacturing a sulfide-based solid electrolyte includes preparing a single substance lithium, a single substance sulfur, and a P 2 S 5 and a step (S10) of preparing raw materials of lithium halide (LiX), a step (S20) of introducing the raw materials into a solvent and stirring the mixture, a step (S30) of drying the stirred mixture, and a step (S40) of heat-treating the dried material.

[0056] The raw material is characterized in that the raw material includes elemental lithium and elemental sulfur. In the exemplary embodiment, "elemental" refers to a substance composed of a single element, thus exhibiting its inherent chemical properties. Therefore, elemental lithium is a substance composed only of lithium elements, thus exhibiting its inherent chemical properties, and elemental sulfur is a substance composed only of sulfur elements, thus exhibiting its inherent chemical properties.

[0057] As described above, in the sulfide-based solid electrolyte, the molar ratio (S / P) of sulfur element (S) to phosphorus element (P) is 5 to 7, preferably 6 to 7, which is higher than that of the conventional sulfide-based solid electrolyte. In order to manufacture the above-mentioned sulfide-based solid electrolyte, the present invention is characterized in that, in addition to P 2 S 5 In addition, elemental sulfur is also used as a raw material.

[0058] Therefore, the sulfur element contained in the sulfide-based solid electrolyte is derived from a material selected from elemental sulfur, P 2 S 5 and combinations thereof.

[0059] The raw material may also include a selected from Li 2 At least one of S, elemental phosphorus, elemental halogen molecules, and combinations thereof. In order to easily compound a sulfide-based solid electrolyte having a specific composition, a single element may be used instead of a compound.

[0060] The step of preparing the raw material may include mixing simple lithium, simple sulfur, P according to the composition of the sulfide-based solid electrolyte represented by the above chemical formula 1. 2 S 5 and lithium halide (LiX).

[0061] Subsequently, the prepared raw material is introduced into a solvent, and the mixture is stirred (S20).

[0062] Any solvent may be used without limitation as long as the solvent can dissolve the raw material. For example, the solvent may be selected from methanol, ethanol, propanol, butanol, dimethyl carbonate, ethyl acetate, tetrahydrofuran, 1,2-dimethoxyethane, propylene glycol dimethyl ether, acetonitrile, and combinations thereof.

[0063] When the raw material is introduced into the solvent and then the mixture is stirred, the raw material is dissolved in the solvent, and the components of the raw material react with each other, thereby composite sulfide-based solid electrolyte. The stirring conditions are not particularly limited. The stirring can be carried out under the conditions of the stirring speed and stirring time required for the raw material to be fully dissolved in the solvent.

[0064] The step (S30) of drying the stirred mixture is a step of removing the solvent.

[0065] The drying step (S30) may be performed under conditions that do not deteriorate the sulfide-based solid electrolyte compounded in the stirring step (S20). For example, vacuum drying may be performed under conditions of 25 to 200° C. and 2 to 20 hours. Vacuum drying is preferably performed to prevent the sulfide-based solid electrolyte from reacting with external moisture.

[0066] The drying step (S30) may include a first drying performed at 25 to 45° C. and 1 to 3 hours, a second drying performed at 50 to 70° C. and 1 to 3 hours, a third drying performed at 100 to 120° C. and 1 to 3 hours, a fourth drying performed at 150 to 170° C. and 1 to 3 hours, and a fifth drying performed at 200 to 220° C. and 1 to 3 hours. The drying steps may be performed continuously from the first drying to the fifth drying. Since the drying is performed while the temperature is gradually increased, the solvent can be removed more quickly and efficiently.

[0067] The step (S40) of heat-treating the dried material is a step of growing a crystalline phase of the sulfide solid electrolyte. In the stirring step (S20) and the drying step (S30), the sulfide solid electrolyte is amorphous. When the amorphous sulfide solid electrolyte is heat-treated, a crystalline sulfide solid electrolyte having an Argentum-type crystal structure can be obtained.

[0068] The heat treatment step (S40) may be performed at 400-600°C for 1-10 hours. When the heat treatment conditions are the same as above, the crystal phase of the sulfide-based solid electrolyte can be sufficiently grown without deteriorating the amorphous sulfide-based solid electrolyte.

[0069] Hereinafter, the present invention will be described in more detail with reference to specific examples. However, the following examples are only illustrative for helping to understand the present invention, and the present invention is not limited to the following examples.

[0070] Example - Li 3.5 PS 7 Composition of Br

[0071] (S10) weighing elemental lithium (powder), elemental sulfur (powder), P 2 S 5 and LiBr (product of Sigma-Aldrich) to prepare the raw materials, so that the finally obtained sulfide-based solid electrolyte has the composition of the embodiment shown in Table 1 below.

[0072] (S20) The raw material is introduced into acetonitrile (solvent), and the mixture is stirred.

[0073] (S30) The stirred mixture is vacuum dried at about 200° C. for about 2 hours to remove the solvent.

[0074] (S40) The dried material is heat-treated at about 550°C for about 5 hours to obtain a crystallized sulfide-based solid electrolyte.

[0075] Comparative Example - Li 6 PS 5 Composition of Br

[0076] The sulfide solid electrolyte was prepared by the same method as in Example 1, except that Li 2 S.P. 2 S 5 and LiBr (product of Sigma-Aldrich) to prepare raw materials, so that the finally obtained sulfide-based solid electrolyte has a composition of a comparative example shown in the following Table 1.

[0077] Experimental Example 1 - Evaluation of ionic and electronic conductivity

[0078] The ionic conductivity and electronic conductivity of each sulfide-based solid electrolyte according to the embodiment and the comparative example were measured. Each sulfide-based solid electrolyte was pressed to form a sample for measurement (13 mm in diameter and 0.6 mm in thickness). An alternating potential of 10 mV was applied to the sample, and then 1×10 6 The frequency was scanned from 100 Hz to 100 Hz to measure the impedance value, thereby determining the ionic conductivity and electronic conductivity. The results are shown in Table 1.

[0079] Referring to Table 1, it can be seen that the sulfide-based solid electrolyte according to the example exhibits ion conductivity comparable to that of a conventional solid electrolyte, and exhibits much higher electron conductivity than that of a conventional solid electrolyte.

[0080] Experimental Example 2 - Evaluation of discharge capacity and charge efficiency

[0081] A battery for evaluation was manufactured using each of the sulfide-based solid electrolytes according to Examples and Comparative Examples as follows.

[0082] (Formation of Negative Electrode) A negative electrode slurry was prepared, which contained a negative electrode active material, a solid electrolyte, a conductive agent, and a binder in a weight ratio of 50:40:5:5. Graphite (Hitachi, 23 μm) was used as the negative electrode active material, a sulfide-based solid electrolyte was used as the solid electrolyte, Super C (Timcal, 40 nm) was used as the conductive agent, and an acryl-based binder (Zeon, model name: SX-9334) was used as the binder.

[0083] 7.2 g of the negative electrode slurry was applied to a substrate using a doctor blade coating method and then dried using an oven in a glove box to manufacture a negative electrode.

[0084] (Formation of Solid Electrolyte Layer) A solid electrolyte layer slurry was prepared, which contained a solid electrolyte and a binder at a weight ratio of 97:3. A sulfide-based solid electrolyte was used as the solid electrolyte, and an acryl-based binder (Zeon Corporation, model name: SX-9334) was used as the binder.

[0085] 6.8 g of the solid electrolyte layer slurry was applied to the negative electrode using a doctor blade coating method to a thickness of about 500 μm, and then dried to produce a negative electrode-solid electrolyte layer composite. All of the above processes were performed in a glove box.

[0086] (Formation of all-solid-state battery) First, the negative electrode-solid electrolyte layer composite is punched into a to prepare a composite negative electrode. The Li-In electrode (the negative electrode) is placed The mold is placed on the composite negative electrode so that the collector faces upward. Subsequently, the molds are connected and pressed using a granulator to obtain a battery.

[0087] The battery was tested for charge and discharge. Specifically, charging was performed under CC-CV conditions, and discharging was performed under CC conditions. Voltages from -0.62 to 1.38 V were evaluated. In the constant current mode, the current amount was 40 μA / cell, and the test was performed until the constant voltage dropped to about 20% of the existing current amount (40 μA / cell). The results were Figure 3 and are shown in Table 1.

[0088] [Table 1]

[0089]

[0090] "Charge efficiency" refers to the ratio of the amount of electricity discharged to the amount of electricity charged during one charge-discharge cycle. The charge efficiency can be determined using the following formula.

[0091] Charging efficiency [%] = Discharged capacity / Charged capacity × 100

[0092] From the above results, it can be seen that when the sulfide-based solid electrolyte according to the exemplary embodiment of the present invention is used for the negative electrode, the discharge capacity is about 40% higher than that of the conventional solid electrolyte, and the charge efficiency is about 8% higher than that of the conventional solid electrolyte.

[0093] Experimental Example 3—Evaluation using X-ray Photoelectron Spectroscopy (XPS).

[0094] The sulfide-based solid electrolyte according to the embodiment was analyzed using X-ray photoelectron spectroscopy. Figure 4 Shown in.

[0095] Referring to the figure, peaks are found when the binding energy is about 131.72 eV (③) and 132.9 eV (②). Therefore, it can be seen that the sulfide-based solid electrolyte according to the exemplary embodiment of the present invention includes the negative ion cluster P 2 S 7 4- .

[0096] As is apparent from the foregoing, in the case where the sulfide-based solid electrolyte according to the exemplary embodiment of the present invention is used for the negative electrode of the all-solid-state battery, the discharge capacity of the all-solid-state battery can be greatly increased.

[0097] The effects of the present invention are not limited to the above-mentioned effects. It can be understood that the effects of the present invention include all the effects that can be inferred from the foregoing description of the present invention.

[0098] The invention has been described in detail with reference to exemplary embodiments thereof. However, it will be appreciated by those skilled in the art that changes may be made in these embodiments without departing from the principles and spirit of the invention as defined by the claims and their equivalents.

Claims

1. A sulfide solid electrolyte suitable for all-solid-state battery electrodes, comprising: Lithium element Li, sulfur element S, phosphorus element P and halogen element X, Wherein, the halogen element X is selected from chlorine element Cl, bromine element Br and a combination thereof, Wherein, the sulfide solid electrolyte is represented by the following chemical formula: Li a PS b X c Among them, 3≤a≤3.5, 6≤b≤7, and 1≤c≤2, Wherein, the sulfide solid electrolyte includes negative ion cluster P2S7 4- , The sulfide-based solid electrolyte has an argyrodite-based crystal structure.

2. An all-solid-state battery, comprising: positive electrode; negative electrode; as well as a solid electrolyte layer disposed between the positive electrode and the negative electrode, Wherein, the negative electrode comprises the sulfide-based solid electrolyte according to claim 1.

3. An all-solid-state battery, comprising: positive electrode; negative electrode; as well as a solid electrolyte layer disposed between the positive electrode and the negative electrode, Wherein, the positive electrode comprises the sulfide-based solid electrolyte according to claim 1.

4. A method for manufacturing a sulfide-based solid electrolyte suitable for an all-solid-state battery electrode, the method comprising the following steps: Prepare raw materials including elemental lithium, elemental sulfur, P2S5 and lithium halide LiX; introducing the raw material into a solvent and stirring the mixture of the raw material and the solvent to dissolve the raw material; drying the stirred mixture; and The dried material is heat treated. Wherein, the sulfide solid electrolyte includes sulfur element S, which is derived from at least one selected from the elemental sulfur, the P2S5 and a combination thereof, Wherein, the halogen element X is selected from chlorine element Cl, bromine element Br and a combination thereof, The step of preparing the raw material includes mixing elemental lithium, elemental sulfur, P2S5 and lithium halide LiX according to the composition of the sulfide solid electrolyte represented by the following chemical formula: Li a PS b X c Among them, 3≤a≤3.5, 6≤b≤7, and 1≤c≤2, Wherein, the sulfide solid electrolyte includes negative ion cluster P2S7 4- , The sulfide-based solid electrolyte has an argyrodite-based crystal structure.

5. The method according to claim 4, wherein: The raw material also includes at least one selected from Li2S, elemental phosphorus, elemental halogen molecules and combinations thereof.

6. The method according to claim 4, wherein: The solvent is selected from the group consisting of methanol, ethanol, propanol, butanol, dimethyl carbonate, ethyl acetate, tetrahydrofuran, 1,2-dimethoxyethane, propylene glycol dimethyl ether, acetonitrile and combinations thereof.

7. The method according to claim 4, wherein: The step of drying the stirred mixture includes vacuum drying under the conditions of 25 to 200° C. and 2 to 20 hours.

8. The method according to claim 4, wherein: The step of drying the stirred mixture comprises: First drying at 25-45°C for 1-3 hours; Second drying at 50-70°C for 1-3 hours; The third drying is carried out at 100-120° C. and 1-3 hours; A fourth drying performed at 150 to 170° C. for 1 to 3 hours; and The fifth drying is performed under the conditions of 200 to 220° C. and 1 to 3 hours.

9. The method according to claim 4, wherein: The step of heat-treating the dried material is performed under the conditions of 400 to 600° C. and 1 to 10 hours.

Citation Information

Patent Citations

  • Lithium, phosphorus, sulfur, and iodine including electrolyte and catholyte compositions, electrolyte membranes for electrochemical devices, and annealing methods of making these electrolytes and catholytes

    CN108604705A

  • Manufacturing method of solid electrolyte

    JP2017010936A